A boundary approximation algorithm for distributed sensor networks. (8th July 2010) - Ham, M.I.; Rodriguez, M.A.
We present an algorithm for boundary approximation in locally linked sensor networks that communicate with a remote monitoring station. Delaunay triangulations and Voronoi diagrams are used to generate a sensor communication network and define boundary segments between sensors, respectively. The proposed algorithm reduces remote station communication by approximating boundaries via a decentralised computation executed within the network. Moreover, the algorithm identifies boundaries based on differences between neighbouring sensor readings, not absolute sensor values. An analysis of the bandwidth consumption of the algorithm is presented and compared to two naive approaches. The proposed algorithm reduces the amount of remote communication (compared to the naive approaches) and becomes increasingly useful in networks with more nodes.